Knockdown of Unconventional Myosin ID Expression Induced Morphological Change in Oligodendrocytes - Yamazaki, Reiji (SAGE Publications, 2016)
Myelin is a special multilamellar structure involved in various functions in the nervous system. In the central nervous system, the oligodendrocyte (OL) produces myelin and has a unique morphology. OLs have a dynamic membrane sorting system associated with cytoskeletal organization, which aids in the production of myelin. Recently, it was reported that the assembly and disassembly of actin filaments is crucial for myelination. However, the partner myosin molecule which associates with actin filaments during the myelination process has not yet been identified. One candidate myosin is unconventional myosin ID (Myo1d) which is distributed throughout central nervous system myelin; however, its function is still unclear. We report here that Myo1d is expressed during later stages of OL differentiation, together with myelin proteolipid protein (PLP). In addition, Myo1d is distributed at the leading edge of the myelin-like membrane in cultured OL, colocalizing mainly with actin filaments, 2′,3′-cyclic nucleotide phosphodiesterase and partially with PLP. Myo1d-knockdown with specific siRNA induces significant morphological changes such as the retraction of processes and degeneration of myelin-like membrane, and finally apoptosis. Furthermore, loss of Myo1d by siRNA results in the impairment of intracellular PLP transport. Together, these results suggest that Myo1d may contribute to membrane dynamics either in wrapping or transporting of myelin membrane proteins during formation and maintenance of myelin.